2012
DOI: 10.1002/ajmg.a.35558
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense CDK5RAP2 mutation in a Somali child with primary microcephaly and sensorineural hearing loss

Abstract: Primary microcephaly is a genetically heterogeneous condition characterized by reduced head circumference (−3 SDS or more) and mild-to-moderate learning disability. Here, we describe clinical and molecular investigations of a microcephalic child with sensorineural hearing loss. Although consanguinity was unreported initially, detection of 13.7 Mb of copy neutral loss of heterozygosity (cnLOH) on chromosome 9 implicated the CDK5RAP2 gene. Targeted sequencing identified a homozygous E234X mutation, only the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
4
27
0
1
Order By: Relevance
“…Further tests did not reveal any significant hearing impairment or epilepsy as a cause for the speech deficit. Therefore, although sensorineural hearing loss has been reported in two patients with mutations in CDK5RAP2 [5,15], this is not a consistent finding in MCPH3. Both patients had microcephaly, simplified gyral pattern of the cerebral cortex, with shallow sulci anteriorly and deep sulci parietally and posteriorly, and corpus callosum hypogensis on cMRI.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Further tests did not reveal any significant hearing impairment or epilepsy as a cause for the speech deficit. Therefore, although sensorineural hearing loss has been reported in two patients with mutations in CDK5RAP2 [5,15], this is not a consistent finding in MCPH3. Both patients had microcephaly, simplified gyral pattern of the cerebral cortex, with shallow sulci anteriorly and deep sulci parietally and posteriorly, and corpus callosum hypogensis on cMRI.…”
Section: Discussionmentioning
confidence: 92%
“…Homozygous mutations of the Cyclin-dependent kinase 5 regulatory subunit-associated protein 2 gene, CDK5RAP2 (OMIM*608201), were identified in 2005 as a cause for MCPH type 3 (MCPH3, OMIM#604804) [3]. To date, three different mutations have been identified: two in three Pakistani families and one mutation in a Somali patient: (i) a nonsense mutation in exon 4 (c.246T > A, p.Y82X), (ii) an A to G transition in intron 26 (c.4005-15A > G, p.R1334SfsX5) introducing a new splice acceptor site, a frame shift and a premature stop codon, and (iii) a nonsense mutation in exon 8 (c.700G > T, p.E234X) [3-5]. All three mutations have been proposed, but not shown, to lead to a truncated protein and a loss of CDK5RAP2 function.…”
Section: Introductionmentioning
confidence: 99%
“…11 To date, splicing, homozygous nonsense and compound heterozygous mutations for which both of the mutations were predicted to result into CDK5RAP2 protein truncation have been described in MCPH cases, sometimes concomitantly with agenesis, hypogenesis or abnormalities of the corpus callosum. 4,[12][13][14][15][16] In parallel, it was shown that other MCPH patients with mutations in ASPM (MCPH5) or WDR62 (MCPH2) can also exhibit ACC and that a patient with microcephaly harboring a missense in the Microcephalin gene (MCPH1) presented a less severe clinical phenotype compared with the patients with truncating mutations in the same gene. [17][18][19] We might therefore propose that mutations completely abolishing CDK5RAP2 protein function, such as nonsense or frameshift mutations, would lead to a microcephaly phenotype, whereas recessive missense mutations, where there may be some residual function, might result in a different phenotype such as isolated ACC.…”
Section: Discussionmentioning
confidence: 98%
“…Autosomal recessive primary microcephaly (MCPH) is a rare phenotype characterized by a occipitofrontal circumference (OFC) at birth measuring less than at least three standard deviations (SD) below the mean [Verloes et al; Pagnamenta et al, ]. Individuals have reduced brain size, varied intellectual deficit without major cortical architecture abnormalities, absence of other organ malformations, and typically normal facial appearance aside from a sloping forehead that may accompany small cranial size [Issa et al, ; Mahmood et al, ; Hassan et al, ; Woods et al, ; Issa et al, ], which may help distinguish MCPH from other syndromic disorders associated with microcephaly .…”
Section: To the Editormentioning
confidence: 99%